Hospital Inpatient Admissions With Dehydration and/or Malnutrition in Medicare Beneficiaries Receiving Enteral Nutrition: A Cohort Study. Issue 4 (22nd December 2017) - Drake, Rachel; Ozols, Audrey; Nadeau, William J.; Braid‐Forbes, Mary Jo
Abstract: Background : Enteral nutrition (EN) supports many older and disabled Americans. This study describes the frequency and cost of acute care hospitalization with dehydration and/or malnutrition of Medicare beneficiaries receiving EN, focusing on those receiving home EN. Methods : Medicare 5% Standard Analytic Files were used to determine Medicare spending for EN supplies and the proportion and cost of beneficiaries receiving EN, specifically home EN, admitted to the hospital with dehydration and/or malnutrition. Results : In 2013, Medicare paid $370, 549, 760 to provide EN supplies for 125, 440 beneficiaries, 55% of whom were also eligible for Medicaid. Acute care hospitalization with dehydration and/or malnutrition occurred in 43, 180 beneficiaries receiving EN. The most common principal diagnoses were septicemia (21%), aspiration pneumonitis (9%), and pneumonia (5%). In beneficiaries receiving EN at home, >one‐third (37%) were admitted with dehydration and/or malnutrition during a mean observation interval of 231 ± 187 days. Admitted patients were usually hospitalized more than once with dehydration and/or malnutrition (1.73 ± 1.30 admissions) costing $23, 579 ± 24, 966 per admitted patient, totaling >$129, 685, 622 during a mean observation interval of 276 ± 187 days. Mortality in the year following enterostomy tube placement was significantly higher for admitted compared with nonadmitted patients (40% vs 33%; P = .05). Conclusion : Acute care hospitalizations with dehydration and/or malnutrition in Medicare beneficiaries receiving EN were common and expensive. Additional strategies to reduce these, with particular focus on vulnerable populations such as Medicaid‐eligible patients, are needed.